Disparities in driving forces behind energy-related black carbon emission changes across China's provinces. (1st January 2022) - Kang, Ping; Deng, Zhongci; Zhang, Xiaoling; Wang, Zhen; Li, Weijie; Qi, Hong; Lei, Yu; Ou, Yihan; Deng, Zhongren
Abstract: Black carbon (BC) is one of the most important factors affecting the uncertainty of global climate change, as well as affecting human health by absorbing harmful substances in the environment. Understanding how human activities drive BC emissions can help formulate effective emission reduction policies. However, regional differences in social and economic activities determine the factors driving BC emission change in different regions/provinces, leading to the non-applicability of national-level emission reduction policies among the provinces. Therefore, it is necessary to develop a provincial-level analysis to shape refined policies for BC emission reduction. Here, we subdivided China's total BC emissions into 30 provinces based on previous work and used the multi-regional input-output model and complete average decomposition analysis to explore how BC emission intensity, intermediate inputs structural adjustment, local final demand, inter-provincial trade, and international exports drive BC emissions during 2007–2017. The results showed that BC emission intensity was an important emission reduction factor for all provinces in China. As for the effect of intermediate inputs structural adjustment, it had a negative effect during 2007–2012. However, during 2012–2017, as the tertiary industry had become the biggest factor in promoting economic development, the impact of the intermediate input structure on BC emissions had become a positive contribution, which showed that current industrial structure adjustment was not conducive to BC emissions reduction. Local final demand, inter-provincial trade, and international exports were the main factors causing the increase in BC emissions in each province as well. Southwestern regions and heavy industrial provinces emitted additional high BC emissions due to the huge final demand in the Eastern coastal regions. More targeted policies can be formulated by determining BC emission reduction responsibilities based on their driving factors at the provincial and sectoral levels and the development of emission reduction measures for each province. Highlights: BC emission intensity and structural adjustment were the main factors decreasing the emission increment of BC. Local final demand, inter-provincial trade, and exports were the main factors causing the increase in BC emissions. The emission effect of inter-provincial trade gradually concentrated from eastern region to central and western regions.